First steps towards a cyclical theory for LDCs - Roger Bratenstein (Intereconomics, 1974)
The development of the Third World countries which are producers of raw materials and agricultural products has become a cardinal problem of economic science and policy. Concentration on the question what is the best development strategy to obtain maximum growth of the national product has led to neglect of the complex of problems covered by the theory of the economic cycle which attempts to explain the short-term fluctuations of the national product.
Keywords: 330; Economic Cycle